UNDERSTANDING THE LINGUAL FORM OF ANGER EXPRESSION USED BY CHINESE ETHNIC IN PADANG AS THE EFFORT TO BUILD MUTUAL UNDERSTANDING TO PREVENT NATION DISINTEGRATION - Ermanto Ermanto; Emidar Emidar (International Conference on Languages and Arts, 2014)
This study is aimed to reveal the lingual forms of anger expression used by Chinese ethnic in Padang. The research is a qualitative study to examine the problems of humanity. This study uses descriptive linguistic research and synchronic linguistics. The research findings indicate that the form of angry expressions used by speakers of Chinese ethnic in Padang toward the partner are used lingual forms of (1) nouns, (2) verbs, (3) adjectives, and (4) the word archaic. In the Chinese ethnic community, the various forms of the word/phrase in the form of anger expression noun/noun to express the emotion of anger are as follows: (1) noun/noun of spirits; (2) noun/noun of animal; (3) noun/noun of part of the body; (4) noun/noun of negative behavior; (5) noun/noun of another. The form of the word/phrase in the form of anger expression verbs/verb used by the speakers of Chinese ethnic in Padang to express the emotion of anger toward the partners can be divided into (1) action verbs, (1) verbs of action, and (3) the verb (phrase) circumstances. The angry form of lingual adjective form used by the speakers of Chinese ethnic in Padang toward the partners can be divided into three subtypes word adjective  as following: (1) Chinese ethnic’s form of angry in the form of subtype word adjective/adjective pemeri nature (negative); (2) Chinese ethnic’s form of angry in the form of subtype adjective/word mental attitude (negative); (3) Chinese ethnic form of praise in the form of the subtype adjective/adjective perception (negative).   Keywords: anger expression, Chinese, mutual understanding,